Study of trace elements status of breast cancer patients - Tillashaykhov, M.N; Khudaykulov, A.T.; Danilova, E.A.; Usupbekov, A.A.; Alimkhodjaeva, L.T. (Онкологія, 2017)
The last 15 years, the methods of evaluation of trace elements in the human body for the hair analysis have been actively developing. The content of trace elements in hair reflects their level in the human body, and is an integral indicator charac - terizing his element status. Purpose: study of trace elements in patients with second- stage breast cancer. Object and Methods: to determine the content of trace elements, it was stu died the hair of 30 patients with stage II breast cancer who were treated at the Natio nal Cancer Research Center of the Ministry of Health of the Republic of Uzbekistan in 2016. The study of hair samples for content of trace elements (calci - um, potassium, sodium, chlorine, iron, zinc, copper, manganese, cobalt, chromium, selenium, iodine, bromine) was conducted in the laboratory analysis of the activa - tion of the Institute of Nuclear Physics of Uzbekistan Academy of Sciences, instru - mental neutron activation analysis. The received data on the micronutrient content in hair of patients compared with reference values for the population of Uzbekistan, adopted at the Institute of Nuclear Physics. Results: the reduction of iron, zinc, cop - per, cobalt level and high content of chlorine as compared with the reference val - ues were showed. Conclusions: undertaken studies have shown the possibility of us - ing of the results for the primary prevention and identification of risk groups among women, as well as the usefulness of the correction of specialized treatment medica - tion with microelement complexes.